The Role of Parenting Style to the Feeling of Adequately Heard and Subjective Well-Being in Perpetrators and Bullying Victims - Borualogo, Ihsana Sabriani (Jurnal Psikologi, 2021)
This study aimed to explain the contribution of parenting styles on children’s perception of being adequately heard by parents and their subjective well-being across three bullying groups (perpetrators, victims, and uninvolved). Participants (N = 1,294; 54.8% girls; 45.2% boys) were elementary school (47.3%) and junior high school students (52.7%) in Bandung City. Parenting styles were measured using Egna Minnen Beträffande Uppfostran for Children. Subjective well-being was measured using the Children's Worlds Subjective Well-Being Scale. Being adequately heard by parents was measured using the Children's Worlds measure. Data were analysed using linear regression and descriptive analysis. Parenting styles contributed significantly to children’s perception of being heard by parents and their subjective well-being. Parenting styles contributed differently across the three groups and genders. The uninvolved perceived that their parents were warm. The perpetrators perceived their parents as rejective. The victims perceived their parents as overprotective. The perpetrators displayed the lowest SWB score, while the uninvolved displayed the highest SWB score. Warm mothers showed a significant positive effect on children’s SWB and perception that they were adequately heard. Overprotective fathers showed a significant positive effect on children’s SWB because father was perceived as the family's head who protects their children. It is suggested that parents should practice warm rearing to prevent children’s involvement in bullying